Inkuiri Terbimbing Sebagai Cara Meningkatkan Penguasaan Keterampilan Proses Sains Siswa Kelas X MIA SMA - Muhammad Ircham Wildan Sholihan; Maridi Maridi; Joko Ariyanto; Ika Setyanti (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
The purpose of this study is to improve science process skill (SPS) mastery of tenth graders using guided inquiry. Research design is classroom action research. Data taken by direct observation and analyzing the students' worksheet. Student worksheets analyzed by comparing to the SPS indicator from Harlen and Rustaman. Data analysis using descriptive method. It can be concluded that 1) application of guided inquiry can improve the students’ skill mastery. 2) Students will felt uncomfortable when moved from traditional learning class to guided inquiry without prior adaptation, impeding learning process, lowering students' perform and achievement. 3) Inquiry should be applied gradually, based on the condition and situation of the students, particularly when students used to traditional teaching.